PELATIHAN PENGOLAHAN IKAN LELE PADA UMKM BUMI ASRI KOTA BATU - Wuryan Andayani; Bogat Agus Riyono; Purweni Widhianningrum; Sendi Nopita Sari; Dian Anugerah Pancasona; Kartika Setya Febriyanty (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This research aims to improve the capabilities and skills of MSMEs in Bumi Asri, Batu City through training and processing catfish into shredded meat, meatballs, and petty burgers. The Bumi Asri area has great potential in promoting catfish farming through proper processing and increasing the selling value of the products produced. This program is designed holistically to empower micro, small, and medium enterprises (MSMEs) through a series of incentive-based training sessions covering entrepreneurship and techniques for processing local food products that appeal to the market. Various methods were used in the training, including basic training and hands-on practice. Survey results indicate that this catfish processing training program was highly beneficial and received high praise from participants. Most participants assessed that the materials and practices presented were very beneficial, relevant, and significant in line with their needs and expectations. The success of this program underscores the importance of similar initiatives in empowering local communities, enhancing SME capacity, and supporting broader sustainability by improving the management of catfish products (e.g., catfish flakes, petty burgers, and catfish meatballs). However, the challenges faced require efforts to strengthen catfish production as a sustainable approach to improving the local economy.